Pendidikan Islam membangun akhlak generasi bangsa - Indra, Hasbi (Ta'dibuna: Jurnal Pendidikan Islam, 2019)
The paper is a thought about the moral of students it a goal of the National System of Education is to regulate government that UU No. 20 tahun 2003. Morals of students a mission of urgent due it attitudes of Muhammad since before as a prophet messenger in the world. The morality is important for students for Islamic education such as TPQ, Diniyah, Pesantren, Islamic Schools and Islamic Higher of Education, even this time the human be the face of challenges the wave of development of science and technology that effect of positive or negative for the human being. The students' Islamic education now should attitude the huge morality. This research a description of how should Islamic education have response and anticipate the matters of the open community communicate with the other in order the student has its attitudes. The qualitative research is a source of experts in Islamic education through relevant books or journals. Abstrak Artikel ini merupakan pemikiran tentang moral siswa yang menjadi tujuan Sistem Pendidikan Nasional adalah untuk mengatur pemerintah bahwa UU No. 20 tahun 2003. Moral siswa adalah misi yang mendesak karena sikap Muhammad sejak dulu sebagai utusan nabi di Dunia. Moralitas penting bagi siswa untuk pendidikan Islam seperti TPQ, Diniyah, Pesantren, Sekolah Islam dan Pendidikan Tinggi Islam, bahkan saat ini manusia menjadi wajah tantangan gelombang perkembangan ilmu pengetahuan dan teknologi yang berpengaruh positif atau negatif bagi manusia. Pendidikan Islam para siswa sekarang harus bersikap moralitas yang besar. Penelitian ini menggambarkan bagaimana seharusnya pendidikan Islam menanggapi dan mengantisipasi hal-hal dari komunitas terbuka berkomunikasi dengan yang lain agar siswa memiliki sikap. Penelitian kualitatif adalah sumber para ahli dalam pendidikan Islam melalui buku atau jurnal yang relevan. Kata kunci: pendidikan Islam, akhlak, generasi